Interpretasi Konsep Accelerationism; Kapitalisme yang Berjalan dalam Film Interstellar (2014) dan The Platform (2019) - Syahadah, Amalia Utammi; Tambunan, Shuri Mariasih Gietty; Suharjo, Rias Antho Rahmi (Lingua Susastra, 2023)
Accelerationism plays a significant role in advancing scientific knowledge and the framework of human existence. Its contributions are manifested in facilitating convenient and swift access to information sources, digital communication, and the availability of diverse technological tools aiding various professions. On the contrary, accelerationism leads to a series of disparities between capitalism and modernism. It also results in humans losing control over themselves, time, and life and even contributes to destroying species and the environment. The situational analysis of accelerationism in this study aligned with Liu's findings in "On the Accelerationist Critique of the Problem of Capitalist Modernity" (2022), highlighting the inseparable dual nature of accelerationism concerning capitalism and modernism. The fluid and straightforward concept of accelerationism can be observed in popular cultural products such as movies. Movies like Interstellar (2014) and The Platform (2019) encapsulate the concept of accelerationism within the scope of capitalism from varying perspectives.This content-analysis study aimed to distinguish the interpretations of accelerationism within Interstellar and The Platform as portrayed through scenes, dialogues, and other cinematic elements. The findings of the study, which employed a qualitative descriptive approach, were the interpretation of accelerationism within certain scenes of Interstellar depicting Earth's demise and the agenda of rescuing humanity by journeying to another planet. Accelerationism was also interpreted through dialogues and metaphorical scenes illustrating the concept of the capitalist food-chain mechanism in the prison cells of The Platform.